Rekomendasi Supplement Learning Resources dalam E-Learning berbasis Fuzzy AHP - Anastasia L Maukar; Fitri Marisa; Ahmad Farhan; Ibnu Khalim; Inayati Sa’adah; Mas ‘Edi; Muchamad Roni; Moch. Fajar (Universitas Merdeka Malang, 2021)
Determining effective supporting learning sources in E-Learning is a complex problem because decisions are given to various criteria aimed at giving priority to the alternatives used. The Fuzzy-Analytic Hierarchy Process (Fuzzy AHP) approach is one of the procedures that can be a solution to this problem. This method can be used to determine decisions in the assessment of pre-existing criteria. From the calculation of the tests carried out, YouTube got the highest ranking, and then below it was followed by Google, Brainly, and finally Slide Player. From these calculations, it can be concluded that YouTube can be used as a supporting learning source in the E-Learning learning system.